2004
DOI: 10.1182/blood-2004-02-0712
|View full text |Cite
|
Sign up to set email alerts
|

Identifying and characterizing a novel activating mutation of the FLT3 tyrosine kinase in AML

Abstract: The FLT3 receptor is activated by juxtamembrane insertion mutations and by activation loop point mutations in patients with acute myeloid leukemia (AML). In a systematic tyrosine kinase gene exon resequencing study, 21 of 24 FLT3 exons were sequenced in samples from 53 patients with AML, 9 patients with acute lymphoblastic leukemia (ALL), and 3 patients with myelodysplasia samples. Three patients had novel point mutations at residue N841 that resulted in a change to isoleucine in 2 samples and to tyrosine in 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(59 citation statements)
references
References 22 publications
2
57
0
Order By: Relevance
“…The Tyr599Phe point mutation is a novel one, which has not been previously reported among cell lines nor patients with FLT3 mutations. 34,35 Interestingly, the Tyr599Phe and seven-codon duplication were found in the same allele. An ITD of 30 bp found in MV4-11 cells resulted in an additional histidine in the middle of the duplication.…”
Section: Discussionmentioning
confidence: 92%
“…The Tyr599Phe point mutation is a novel one, which has not been previously reported among cell lines nor patients with FLT3 mutations. 34,35 Interestingly, the Tyr599Phe and seven-codon duplication were found in the same allele. An ITD of 30 bp found in MV4-11 cells resulted in an additional histidine in the middle of the duplication.…”
Section: Discussionmentioning
confidence: 92%
“…Ba/F3 cells rely on continuous supplementation of recombinant interleukin-3 (IL-3) for their growth; introduction of dominant oncogenes renders these cells IL-3 independent (Azam et al, 2003;Jiang et al, 2004). Ba/F3 cells therefore represent an ideal model to assay for oncogenicity and to analyse different oncogene mutants for their sensitivity to targeted drugs.…”
Section: Resultsmentioning
confidence: 99%
“…PCR-RFLP (restriction fragment length polymorphism) using EcoRV is one of the methods of detection for FLT3-TKD. It is important to note that digestion by EcoRV could not detect all FLT3-TKD mutations (13), however, sequence analysis showed that 50 -68% of FLT3-TKD mutations were substitutions of the first nucleotide of codon D835, most commonly from G to T (14). Traditionally, FLT3-ITD, FLT3-TKD, and NPM1 mutations are detected by PCR followed by electrophoresis or Taqman RQ-PCR (15).…”
Section: Issn: 2320-5407mentioning
confidence: 99%